Successive algorithm for construction of equation of motion of constrained mechanical systems - Phong, Dinh Van (Vietnam Journal of Mechanics, 2002)
The article devotes to the construction of equations of motion of constrained mechanical systems. The constraint conditions are successively appended to the already defined systems. Therefore the algorithm is very flexible and allows studying the separate constraints more in detail. For illustration of consequent steps of the algorithm one simple example is shown.